Synthesis of hydroxy-functional PMMA macromonomers by anionic polymerization - Dhara, Mahua Ganguly; Sivaram, Swaminathan; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2009)
Living anionic polymerization has been utilized to synthesize hydroxy end-functionalized PMMA macromonomers with styryl or allyl functionalities as the polymerizable end-groups. Protected hydroxy-functionalized alkyl lithium initiators have been used to initiate anionic polymerization of MMA. Subsequently the living chains with protected hydroxyl function have been terminated using 4-vinylbenzyl chloride (4-VBC) or allyl methacrylate (ALMA) to form -hydroxy–styryl and -hydroxy–allyl PMMA, respectively. These protected hydroxy-functionalized PMMA macromonomers have been characterized by GPC and 1H-NMR. Termination using 4-VBC led to 50% functionalization, whereas that using allyl methacrylate led to 100% functionalization of the hydroxy-PMMA.
Keywords: Anionic polymerization; functionalized initiator; Macromonomer